A case of TDP-43 type C pathology presenting as nonfluent variant primary progressive aphasia. Issue 1 (2nd January 2020) - Adams-Carr, Kerala L; Bocchetta, Martina; Neason, Mollie; Holton, Janice L; Lashley, Tammaryn; Warren, Jason D; Rohrer, Jonathan D
ABSTRACT: We report a case of rapidly progressive nonfluent variant PPA (nfvPPA), age at onset 77 years old and disease duration 3.3 years, who came to post mortem and was found to have TDP-43 type C pathology, an unusual finding for nfvPPA. All prior TDP-43 type C cases from the UCL FTD cohort (n=25) had a semantic variant PPA (svPPA) phenotype, with all having a younger age at onset and longer disease duration than the nfvPPA case. Volumetric analysis of MRI from the nfvPPA case, twelve of the svPPA cases and ten age-matched controls was performed. Whilst left frontal and insular volumes were lower in the nfvPPA case compared with svPPA,  cortical and medial temporal lobe volumes were lower (particularly on the right) in the svPPA group compared with the nfvPPA patient. Such anatomical involvement is likely to be consistent with the presence of a nonfluent aphasia (left frontal lobe and insula), and only mild semantic deficit early in the illness (left but not right temporal lobe). Such unique cases add to the heterogeneity of the FTD spectrum.